A METHOD FOR MULTI-CRITERIA DECISION MAKING UNDER UNCERTAINTY - Gevorgyan, A.A.; Avagyan, H.S. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2018)
This work presents development of a method for multi-criteria decision making under uncertainty conditions based on single-attribute value functions and probabilistic distributions. The values of different criteria are modeled using normal distributions, i.e. the value of the $ i $-th criteria of the $ j $-th option is given by $ x^j_i \sim \mathcal{N} (μ^j_i, σ^j_i) $ distribution. The method is evaluated and the results are analyzed on a simple example.
Keywords: decision maker; multi-attribute value theory (MAVT); normal distribution; evaluation criteria